The diagnostic performance of CT pulmonary angiography in the detection of chronic thromboembolic pulmonary hypertension-systematic review and meta-analysis - Lambert, Lukas; Michalek, Pavel; Burgetova, Andrea (European radiology, 2022)
OBJECTIVES: To examine the diagnostic performance of CT of the pulmonary artery (CTPA) as a potential first-choice imaging modality in patients with pulmonary arterial hypertension and suspected chronic thromboembolic pulmonary hypertension (CTEPH). METHODS: A systematic review and meta-analysis were conducted in accordance with the PRISMA reporting checklist. Six scientific databases and registers (PubMed, EMBASE, Scopus, Web of Science, Cochrane, ClinicalTrials.gov ) were searched for studies evaluating the diagnostic performance of CTPA in suspected CTEPH in adult patients. Results were pooled separately for studies based on the evaluation of the pulmonary artery and those that relied solely on changes in parenchymal perfusion. RESULTS: Ten single-center studies with 734 patients were eligible for pooling of the diagnostic performance of CTPA by evaluation of the pulmonary artery. The pooled sensitivity, specificity, PPV, NPV, accuracy, and diagnostic odds ratio (DOR) estimates for CTPA in the detection of CTEPH were 0.98, 0.99, 0.94, 1.00, 0.96, 0.96, and 292. Evaluation of perfusion changes yielded pooled estimates for sensitivity, specificity, PPV, NPV, accuracy, and DOR of 0.99, 0.84, 0.79, 0.98, 0.89, 0.89, and 98 across four studies with 278 patients. Scintigraphy, SPECT, digital subtraction angiography, right heart catheterization, pulmonary endarterectomy, and international guidelines were used to establish the diagnosis. CONCLUSION: CTPA has high sensitivity and specificity in the detection of CTEPH when the examination is evaluated by expert radiologists. Evaluation of parenchymal perfusion alone is associated with slightly lower specificity. Further research is needed to determine the diagnostic performance of CTPA in excluding CTEPH in general radiology departments. KEY POINTS: • CT pulmonary angiography (CTPA) is recommended in the diagnostic workup of chronic thromboembolic pulmonary hypertension (CTEPH). • CTPA has high sensitivity and specificity in the detection of CTEPH when evaluated by an expert radiologist. • Evaluation of changes in parenchymal perfusion alone is associated with slightly lower specificity. • Little is known about the diagnostic performance of CTPA in the detection of CTEPH in general radiology departments.
Keywords: Pulmonary Embolism; Pulmonary embolism; Computed tomography angiography; Chronic Disease; chronická nemoc; digitální subtrakční angiografie; plicní embolie; Hypertension, Pulmonary; Sensitivity and Specificity; Adult; Meta-analysis, systematic review; plicní hypertenze; Humans; CT angiografie; Pulmonary arterial hypertension; Computed Tomography Angiography; senzitivita a specificita; Angiography, Digital Subtraction; dospělí; lidé